A DIGITAL APPROACH FOR THE ANALYSIS OF THE OPTICAL COHERENCE TOMOGRAPHY EVALUATION OF HYDROXYAPATITE - BASED BONE GRAFT MATERIALS - Maria Alexandra Rădoi (Drăghici); Eugen Osiac; Luana Corina Lascu; Oana Gîngu; Ioana Mitruț; Alex Ioan Sălan; Răzvan Mercuț; Iulian Antoniac; Horia Octavian Manolea (Romanian Society of Oral Rehabilitation, 2023)
The aim of this study was to evaluate by means of coherence optical tomography (OCT) two synthetic bone augmentation materials based on hydroxyapatite and to quantify the degree of filling of the experimental cavities created one month and two months after their creation. We made 4 groups of 5 Whistar rats on which we created experimental cavities in calvaria and in the upper maxillary. Samples were obtained after one months for two study group and after two months for the other two. After obtaining the images from the optical coherence tomography examination, they were analysed with the ImageJ software. The results provided important information related to the healing pattern of the experimental cavities, the degree of their filling with newly formed bone tissue, but also about the presence of residual particles of synthetic bone graft materials.The increased refractive index of a synthetic bone augmentation material is an important advantage in assessing by OCT the presence of material particles in a bone cavity. The maxillary bone anatomy due to its convexities made more difficult the evaluation of the samples from this area compared to the flat surfaces offered by the calvaria samples. Optical coherence tomography remains a promising method for the evaluation of new-forming bone tissue when synthetic bone graft materials are used, both for research evaluation in order to compare different materials, but also for the potential to be used in clinical activity as well.